Saving Fallen Women Now? Critical Perspectives on Engagement and Support Orders and their Policy of Forced Welfarism. Issue 1 (27th August 2014) - Carline, Anna; Scoular, Jane
Abstract : The UK seems set to follow the increasingly abolitionist trend that is taking hold in Europe in response to the issue of prostitution. While some argue that an abolitionist approach signals a serious attempt to tackle the injustices and gendered aspects of commercial sex, we are less optimistic. Drawing upon the findings of the first study to evaluate Engagement and Support Orders, we argue that any focus on women's needs is distorted by the continued zero tolerance approach to street sex work and the criminal justice setting it takes place in. New revolving doors have been created for those involved in the most visible sectors of the industry and support agencies have been made to take on an increased policing role. This narrow focus individualises the causes of poverty and prostitution, elides the wider structural factors that shape sex work and does little to address the real needs of this vulnerable group. In conclusion, we argue that future policy should engage more productively with the rich cultural study of sex work. This will enable the development of ground-up responses and allow for a more effective role for the criminal law.